Political Dimensions of International Sports and Economic Policies for AI Adoption - Aminova Aziza; Umurkulova Dilrabo; Komilov Jahongir (SHS Web of Conferences, 2025)
In this transformative era, Artificial Intelligence (AI) technologies have emerged as a possible prescription in the global economic and sports governance landscape. Scholars have noted that AI-driven decision-making is transforming the policies, regulatory frameworks, and the economic, social, and political dynamics of international sports and economic policies across the global arena. The paper attempts to move forward research in AI adoption from theoretical, empirical, and policy-driven contexts to emerging methodological frameworks that address current challenges in governance and strategic implementation. The authors propose a multidisciplinary approach that includes AHP-SEM particularly suited for the iterative evaluation, validation, and refinement of findings. Additionally, the hybrid analytical framework is used to organize a systematic assessment of decision-making parameters to identify some best practices related to specific policy interventions and AI adoption strategies. This integrative assessment then furthers the examination of the geopolitical and economic implications related to the use of AI-driven frameworks in terms of policy formulation, stakeholder engagement, and regulatory compliance. A closing case finally examines the role of a prominent international governing body in the sports-economic policy nexus that increase the strategic alignment of AI-integrated sports governance models operating using the data-driven regulatory approach based on the aforementioned methodological insights.